International research of technical curriculum - Mach, Petr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article’s main topic is the research of primary school technical education in the Czech Republic, in the Federal Republic of Germany and in Slovakia. Modern society cannot do without technical development, information technologies and seeking new sources of energy while maintaining ecological balance. This trend requires essential changes in the system of education. Technical literacy must become an important part of education as early as on the elementary school level. Monitoring and analysis of various approaches to technical education in the countries listed above is one of the key outputs of an international project named World of Work (WOW), which has got the registration number 2015-1-SK01-KA201-008942.
Keywords: international project; technical education curriculum; status analysis; SWOT analysis